Peroxisomal Dysfunction Contributes to White Matter Injury Following Subarachnoid Hemorrhage in Rats via Thioredoxin-Interacting Protein-Dependent Manner - Xu, Weilin; Yan, Jun; Chen, Shuda; Ocak, Umut; Shao, Anwen; Zhang, Jianmin (Frontiers in Cell and Developmental Biology, 2020)
Background and Purpose: White matter injury (WMI) exists in the early stage of subarachnoid hemorrhage (SAH) and has not been well addressed. Methods: We utilized shRNA and CRISPR to verify the roles of peroxisomes in WMI following SAH. We evaluated short- and long-term neurobehavior after SAH. Western blotting, immunofluorescence and Golgi staining techniques were performed to assess the changes of protein levels. Results: Catalase (CAT) CRISPR treatment notably attenuated neurological deficits and reduced long-term spatial learning and memory impairments after SAH, by increasing the level of myelin basic protein (MBP) while decreasing the levels of amyloid precursor protein (APP), IL-6 and TNF-α. The use of thioredoxin-interacting protein (TXNIP) shRNA significantly offset the effects of CAT shRNA and use of glycerone phosphate acyl transferase (GNPAT) shRNA significantly reversed the effects of CAT CRISPR by decreasing the levels of plasmalogens and reactive oxidative species (ROS). Conclusions: Peroxisomal dysfunction induced by SAH reversely exacerbated cerebral WMI following SAH, which was at least partly mediated by TXNIP and GNPAT pathways.